2006
DOI: 10.1111/j.1365-2486.2006.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and persistence of common ragweed (Ambrosia artemisiifolia L.) in disturbed soil as a function of an urban–rural macro‐environment

Abstract: No data are available on whether rising carbon dioxide concentration [CO 2 ] or increased air temperature can alter the establishment and persistence of common ragweed (Ambrosia artemisiifolia L.) within a plant community following soil disturbance. To determine ragweed longevity, we exposed disturbed soil with a common seed bank population to an in situ temperature and [CO 2 ] gradient along an urban-rural transect beginning in early 2002. No other consistent differences in meteorological variables (e.g. wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…Population shifts and changes of land use in the proximity of the NAB counting stations may play an important role in determining the amount of airborne pollen collected at the corresponding stations (Haberle et al , 2014, Reid & Gamble, 2009, Ziska & Beggs, 2012). Because of the fertilizer effect of CO 2 in the atmosphere, increase of CO 2 level itself or combined with rising temperature has been reported to substantially influence pollen and spore production (English et al , 2009, Rogers et al , 2010, Ziska et al , 2009, Ziska et al , 2003, Ziska et al , 2007). Data describing these compounding factors (e.g., CO 2 level and land changes) are generally not available or very limited during the period of 1994–2010 for most of the NAB pollen stations.…”
Section: Discussionmentioning
confidence: 99%
“…Population shifts and changes of land use in the proximity of the NAB counting stations may play an important role in determining the amount of airborne pollen collected at the corresponding stations (Haberle et al , 2014, Reid & Gamble, 2009, Ziska & Beggs, 2012). Because of the fertilizer effect of CO 2 in the atmosphere, increase of CO 2 level itself or combined with rising temperature has been reported to substantially influence pollen and spore production (English et al , 2009, Rogers et al , 2010, Ziska et al , 2009, Ziska et al , 2003, Ziska et al , 2007). Data describing these compounding factors (e.g., CO 2 level and land changes) are generally not available or very limited during the period of 1994–2010 for most of the NAB pollen stations.…”
Section: Discussionmentioning
confidence: 99%
“…The development of such an inventory could prove problematical. The presence of ragweed is dependent on soil disturbance (Ziska et al 2007) and so emission inventories require yearly updates due to changes to source characteristics. For instance, changes to land management techniques in agricultural areas, such as increasing the area under grassland, could alter the source strength by displacing ragweed populations.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40] This might reflect the pernicious and ubiquitous nature of ragweed pollen. For example, results from the US National Health and Nutrition Examination Survey show that 26.2% of the US population has a positive skin test response to ragweed.…”
Section: Ragweedmentioning
confidence: 96%
“…38 These data suggested that soil disturbance, in addition to any CO 2 /climate shift, played an essential role in maintaining ragweed populations in urban and suburban environments. 39 Recently, pollen data from the National Allergy Bureau in the United States and the Aerobiology Research Laboratories in Canada were analyzed to determine whether recent warming had resulted in a change in the duration of the ragweed pollen season in North America. 40 These data demonstrated that the duration of the ragweed pollen season has been increasing but only as a function of increasing latitude, which is consistent with differential global warming projected by the IPCC (Fig 1).…”
Section: Ragweedmentioning
confidence: 99%